Determinants of anemia in school-going adolescents: a case study in Douala, Cameroon - Annick Suzanne Mbazoa Mbou; Godfroy Rostant Pokam Djoko; Alice Ketchaji; Sali Aristide Dama; Florence Irita; Verance Carline Kegha Ngodem; Manuela Tchinda Magne; Alex Kevin Tako Djimefo; Joelle Laure Sobngwi (BMC Public Health)
Abstract Context Anemia is a medical condition resulting from a reduction in the number of red blood cells below the reference range. It is a major public health problem, particularly among adolescents, as it can have negative effects on cognitive performance, growth and reproduction. This study aims to assess the determinants of anemia among adolescents in schools in the city of Douala. Methods A cross-sectional study was carried out among 511 adolescents aged 10–15 years, selected by random sampling from four secondary schools in Douala. Data were collected using a structured questionnaire, including anthropometric measurements and hemoglobin tests to assess anemia. Anemia was defined according to specific thresholds (e.g. hemoglobin < 12 g/dL for girls and < 13 g/dL for boys). Severity was classified as mild, moderate and severe. Multiple logistic regression analysis was performed to identify determinants of anemia, controlling for confounding variables, and associations were established by calculating Odds ratios, Odds ratio adjusts, confidence intervals and P-value. Statistical significance was declared at P < 0.05. Results The mean age of participants was 11.9 ± 1.30 years, with a slight predominance of girls (50.7%) over boys (49.3%). The prevalence of anemia was 40.3% (95% CI: 35.0–45.6%), including 15.7% mild anemia (95% CI: 12.0–19.4%), 23.9% moderate anemia (95% CI: 19.7–28.1%) and 0.7% severe anemia (95% CI: 0.1–2.7%). Independent determinants of anemia included rural residence [AOR = 8.39 (95% CI: 5.26–13.65); p < 0.001], status of parents divorced [OR = 2.60 (95% CI: 1.57- 4.34); p = 0.0001] or deceased [AOR = 7.73 (95% CI: 1.65- 41.90); p = 0.011], onset of first menstrual period [AOR = 6.59 (95% CI: 2.28–72.19); p = 0.001], the absence of iron supplementation [AOR = 1.68 (95% CI: 1.04–2.74; p = 0.034] and the occurrence of an illness in the previous three months (malaria, sickle cell disease, viral hepatitis, amoebiasis, typhoid fever, etc.) [AOR = 3.24 (95% CI: 1.14–22.37); p = 0.012]. Conclusions This study highlights a worrying prevalence of anemia among adolescents in Douala, with clearly identified determinants. The results underline the importance of factors such as rural residence, parental status and menarche, which can inform public health policies. It is essential to integrate these elements into targeted intervention programs, particularly in nutrition and iron supplementation, especially in rural areas. Finally, longitudinal studies and intervention-based research are needed to better understand the causal mechanisms of adolescent anemia in this context.